The implementation of Service-Learning Malaysia-University for Society (SULAM) Programme at Universiti Teknologi MARA Perak Branch, Malaysia / Dr. Junainah Mohamad, Prof. Ts. Dr. Norhayati Baharun and Dr. Daljeet Singh Sedhu - Mohamad, Junainah; Baharun, Norhayati; Janah Singh, Daljeet Singh Sedhu (Universiti Teknologi MARA, Kedah, 2024)
This research concentrates on the advantages of implementing the SULAM program among students and lecturers at Universiti Teknologi MARA, Perak Branch Seri Iskandar Campus, Perak Malaysia. This study employed a quantitative approach. The questionnaires were distributed to students and lecturers involved in the SULAM program. The total number of returned questionnaires by students was 107, and 19 by lecturers. The data was subsequently assessed using the Statistical Package for the Social Sciences (SPSS). The results of this research discovered that integrating the SULAM program with the academic curriculum of students and lecturers had positive impacts. These included: 1) students were able to utilize their knowledge and achieve a deeper comprehension of executing a service-learning program, 2) students enhanced their functional work skills, and 3) students demonstrated outstanding ethics and professionalism within the SULAM program at the public university, 4) the lecturers can strengthening the relationship between stakeholders, 5) helps to transform lecturer teaching styles, 6) suitable way to design courses, 7) enhancing lecturer’s teaching ability, productivity, 8) allows lecturers to assist students by offering pertinent practical examples from real-life situations, 9) discover solutions and grasp new concepts and theories, and 10) offers a chance to conduct action research.